RA versus SV Grafts in CABG: Is There a Preferred Strategy? - Sinclair, Heather Q. (MD Conference Express, 2010)
Arterial conduits (particularly the left internal mammary artery [LIMA]) have been shown to be superior to saphenous vein (SV) grafts in terms of long-term patency in patients with coronary artery disease (CAD) who are undergoing coronary artery bypass grafting (CABG). The CABG arm of the prospective, randomized Veterans Administration (VA) Cooperative Study, also known as CSP-474, included 733 patients with stable CAD who were undergoing elective CABG with a LIMA and needed at least one other graft.